Exploring Digital Financial Capability: Evidence From Gen-Z In Surabaya - Pedro Rezo Santoso; Yuanita Ratna Indudewi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This paper explores the financial capability (DFC) of Gen Z in the digital era. Given the rise of digital financial service use during COVID-19, many individuals still lack the necessary skills to manage their finances effectively. The objective of this paper is to examine whether digital financial literacy (DFL) has a significant impact on DFC, with the mediation of digital financial attitude (DFA), financial self-efficacy (FSE), and digital skills (DS). An exploratory was employed, with 98 valid responses from Gen Z participants collected via Google Form. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that DFL has a significant positive effect on DFA and FSE, which in turn positively influence DS. Moreover, DS is found to significantly enhance DFC, establishing the importance of digital skills in the financial domain. These findings underscore the necessity of integrating digital financial education and skills training into programs targeting Gen Z. The study highlights the crucial link between financial literacy and capability in the digital age, suggesting avenues for future research and policy development to enhance financial inclusion and literacy.